Altered Frequency of NK Cells and Treg Cells by Astragalus Polysaccharide Combined with Budesonide in Asthma Model Mice - Wei Zhang; Kuifen Ma (Advances in Polymer Technology)
Objective. We investigated the efficacy of astragalus polysaccharide (APS) combined with budesonide and the effect on expressions of peripheral NK cells and Treg cells and the molecular mechanism in mice with bronchial asthma. Methods. In this study, we established a mouse model of asthma. Four groups of BaLB/C mice were developed; control group had no asthma induction, and the other three groups of mice were sensitized by OVA (Ovalbumin), OVA + budesonide, and OVA + APS + budesonide. Flow cytometry was used to determine the proportion of NK cells and Treg cells. Levels of cytokines IL-4 and IL-10 were detected using RT-PCR and ELISA. Results. Asthma mice treated with APS + budesonide showed alleviated airway resistance compared to model mice (P<0.05). The percentage of dendritic cells (DCs) was reduced (P<0.05), while anti-inflammatory NK cells and Treg cells significantly increased after APS + budesonide treatment (P<0.05). Further, APS + budesonide treatment resulted in improvements in IL-4 and IL-10 mRNA and protein levels (P<0.05). Conclusion. APS combined with budesonide medication may regulate expressions of DCs cells and related cytokines, reliving clinical symptom of bronchial asthma.